Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

irections: Simplify each expressio
25-(√16-1)-(3-9)²


Sagot :

Answer:

-14

Step-by-step explanation:

[tex]\sqrt{16} = 4\\\\(\sqrt{16} - 1) = (4 -1) =3\\\\(3-9) = (-6)\\\\(3-9) ^2 = (-6)^2 = 36\\\\25 - 3 - 36 = 25 - 39 = -14\\[/tex]